STEIN, Steve. Populism in Peru. The emergence of the Masses and the Politics of Social Control The University of Wilconlin Press, Madison, Wisconsin, Estados Unidos. 1980. 296 pgs. - Klaiber, Jeffrey (Histórica, 1981)
No contiene resumen